FAMILY AND MARRIAGE ORIENTATIONS OF MODERN HIGH SCHOOL STUDENTS: STATE AND NECESSITY OF PEDAGOGICAL RESPONSE - Shakhrai, Valentyna (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article exposes the peculiarities of the marriage and family orientations of the modern high school students and highlights the importance of the high school students’ preparation for the future family life.The analysis of the scientific studies that expose the modern process in the marriage and family sphere in Ukraine and around the world is made especially the transition from the traditional model of family to the modern one, the youth’s attitude towards the future family and marriage, points at the importance of the high school students’ preparation for the future family life and parenthood.The aim of the study is to explore the state of the family and marriage orientations of the high school students and to determine the course of the educational work to the improvement of the high school students’ preparation for the future family life and parenthood.The scientific novelty of the study is the determination of the features of family and marriage orientations of high school students primarily in the conditions of the Ukrainian family transformations from the traditional model to the modern one and the determination of the main courses of the family-oriented work with high school students.The investigation was made by using the methods of the analysis of the scientific works, high school students’ questionnaire, generalization, systematization, ranking, grouping, the comparison of the empirical data. It was found that the family takes the high stage in the system of the high school students’ values and orientations. At the same time the high school students’ family and marriage orientations confirm the gradual transition of the Ukrainian family from traditional to the modern one: the delay of the marriage time to more recent time; the preference of having few children; manifestation of the autonomy in choosing of their own family model; tolerance towards the civil marriage; the family break-up admissibility; equality in the family management; acceptance of the premarital relationships. The high school students also have views specific to the traditional family (close relations with parents, the preference of the official marriage, understanding the importance of distribution the family obligations).The conclusion is made that the educational work with the high school students should be oriented at breeding the responsibility, interpersonal relations harmony, reproductive culture. Pedagogical education of parents is necessary to increase parental competence and parental authority. The research made basically confirms the views of scientists about the tendencies of the family and marriage orientations of the modern youth.The article will be useful for the researchers who study the views of the modern youths and the educators who make the corresponding educational work with high school students.